Parasocial Relationships With President Trump as a Predictor of COVID-19 Information Seeking - Kelly, Stephanie; Goke, Ryan; McCall, Mackenzy; Dowell, S. Greg (Frontiers in Communication, 2020)
As the number of COVID-19 cases climbed in the United States, President Trump came under fire for dismissing its severity despite evidence to the contrary. Those most impressionable by the President’s claims might be those who have established a parasocial relationship with him. Results of this survey study indicate that each of the three parasocial variables assessed (i.e., friends, understanding, and brand), were negatively related to information seeking for COVID-19. Moreover, initial evidence was found that identification with the Trump brand was an indirect influence of information seeking. Consistent with the supported model, women and Democrats reported higher information seeking for COVID-19 than men and other political groups.